2019
DOI: 10.1002/ab.21821
|View full text |Cite
|
Sign up to set email alerts
|

“We're not gonna be friends anymore”: Associations between viewing relational aggression on television and relational aggression in text messaging during adolescence

Abstract: A number of studies suggest that adolescents who view relational aggression on television are more likely to engage in higher levels of subsequent relational aggression in social interactions. This research examined longitudinal associations between viewing relational aggression on television and relationally aggressive behavior in text messaging over a one-year period during adolescence. Participants were 197 adolescents who completed a number of questionnaires regarding media use and aggression. Adolescents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Such influence can be negative, particularly regarding aggression and violence and mental health-related outcomes. For example, one study found that viewing aggressive behavior on television was associated with sending aggressive text messages to friends, 50 and several studies found that exposure to the program 13 Reasons Why (which depicted a graphic suicide scene) was associated with suicidal ideation and self-injurious behavior among vulnerable adolescents. Other studies found evidence to support negative influences of exposure to popular television programs on adolescent body image, e-cigarette initiation, and sexual behavior under the influence of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Such influence can be negative, particularly regarding aggression and violence and mental health-related outcomes. For example, one study found that viewing aggressive behavior on television was associated with sending aggressive text messages to friends, 50 and several studies found that exposure to the program 13 Reasons Why (which depicted a graphic suicide scene) was associated with suicidal ideation and self-injurious behavior among vulnerable adolescents. Other studies found evidence to support negative influences of exposure to popular television programs on adolescent body image, e-cigarette initiation, and sexual behavior under the influence of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Relational aggression is carried out directly by threatening to end a relationship or indirectly by spreading rumors/slander about specific individuals to others (Voulgaridou & Kokkinos, 2018). Relational aggression happens in various contexts of interpersonal relations, even in friendship, and several previous studies have examined this in friendship (Bass et al, 2018;Coyne et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary adolescents engage in social aggression with peers in both digital and in-person contexts (Coyne, Ehrenreich, Holmgren, & Underwood, 2019; Underwood, 2003; Underwood & Ehrenreich, 2016), and the extent to which they are exposed to peers’ socially aggressive digital communication may foster the development of their own social aggression. This study examined exposure to peers’ social aggression by capturing the content of every text message that adolescents sent to and received from peers in two 2-day periods.…”
mentioning
confidence: 99%